indonesia - Ahmad Dikin; Jatira; Ghany Heryana (Sekolah Tinggi Teknologi Wastukancana, 2026)
The development of electric vehicles is becoming a trend in the development of global automotive, this is supported by the development of energy storage technology and energy conversion devices that allow for an increase in overall energy efficiency in current electric motor vehicles. Therefore, the study aims to determine the effect of welding strength with 1 mm thick ST40 sphc steel plate material, this material must be tested first for the manufacture of battery casing, one of which is important in making this battery casing by welding, the welding used is SMAW (Shielded Metal Arc Welding), with current variations of 20A, 30A, and 40A. Therefore, it aims to find out which current is good in the welding process itself. With data processing of the two-way ANOVA method. The process of testing the effect of current variations on visual conditions using 40A is better than the others, Tensile Strength ????ℎ????????????????????>???????????????????????? 12.71>5.143, Yield Strength ????ℎ????????????????????>???????????????????????? 7.24>5.143, and elongation ????ℎ????????????????????<???????????????????????? 3.40<5.143.